Pemarkah Kohesi Gramatikal pada Kumpulan Cerpen Bintang Kecil diLangit Kelam Karya Jamal T. Suryanata - Antony, Hevy Metalizka; Juita, Novia; Ngusman, Ngusman (Universitas Negeri Padang, 2012)
This article write to (1) describe the types of grammatical cohesion, (2) describe the grammatical cohesion markers are predominantly used (3) describe the effect of the use of grammatical cohesion markers. The data of this study are sentences containing grammatical cohesion markers. Sources of research data is a collection of short stories works Bintang Kecil di Langit yang Kelam Jamal T. Suryanata. Data were collected by way of reading and marking sentences containing grammatical cohesion markers and advanced engineering techniques as noted. The findings of the study are (1) the type of cohesion markers contained is this reference, substitution, ellipsis and conjuction, (2) types of grammatical cohesion markers are dominant markers used this reference 85%, (3) the effect of using grammatical cohesion contained the discourse coherence of meaning is to make it cohesive and coherent stories.